Thoracoscopic Treatment of Pneumothorax in Marfan Syndrome: Hemostatic Patch to Support Lung Resection Recovery - Gloria Pelizzo; Eloisa Arbustini; Noemi Pasqua; Patrizia Morbini; Valeria Calcaterra (Case Reports in Surgery)
Introduction. In selected patients, the absorbable fibrin patch TachoSil® is superior to standard surgical treatment in reducing air leakage after pulmonary lobectomy. Pulmonary involvement is not considered a main feature of Marfan syndrome (MFS); however, spontaneous pneumothorax (SP) with a high rate of recurrence is frequently reported. We describe the use of TachoSil® in the supportive treatment of recurrent pneumothorax in a girl with MFS. Case Report. A 12-year-old girl with a previous diagnosis of MFS and recurrent history of left spontaneous pneumothorax was submitted to thoracoscopic atypical lung resection. Two patches (9.5 × 4.8 cm) were cut from the adhesive/foam complex (TachoSil®) and were pressed against the sutured area as supportive treatment. The patient recovered with no further SP recurrences. Conclusions. The use of the TachoSil® surgical patch may be useful in pneumothorax supportive treatment, particularly in pediatric MFS by ameliorating the mechanical strength of the lung.